Serological analysis of allergic components of house dust mite provides more insight in epidemiological characteristics and clinical symptom development in North China - Liu, Yi; Zhao, Lan; Wang, Jiaofeng; Guo, Yinshi; Wang, Yifei; Zhang, Lishan; Wu, Zhoujie; Zhu, Mingzhi; Yang, Xukai; Xu, Puyang; Wu, Shandong; Gao, Zhongshan; et al. (Frontiers in Immunology, 2023)
Background House dust mite (HDM) is the most common airborne source causing complex allergy symptoms. There are geographic differences in the allergen molecule sensitization profiles. Serological testing with allergen components may provide more clues for diagnosis and clinical management. Objective This study aims to investigate the sensitization profile of eight HDM allergen components in a large number of patients enrolled in the clinic and to analyze the relation of gender, age, and clinical symptoms in North China. Methods The 548 serum samples of HDM-allergic patients (ImmunoCAP® d1 or d2 IgE ≥0.35) were collected in Beijing City and divided in four different age groups and three allergic symptoms. The specific IgE of HDM allergenic components, Der p 1/Der f 1, Der p 2/Der f 2, Der p 7, Der p 10, Der p 21, and Der p 23, was measured using the micro-arrayed allergen test kit developed by Hangzhou Zheda Dixun Biological Gene Engineering Co., Ltd. The new system was validated by comparing to single-component Der p 1, Der p 2, and Der p 23 tests by ImmunoCAP in 39 sera. The epidemiological study of these IgE profiles and the relation to age and clinical phenotypes were analyzed. Results A greater proportion of male patients was in the younger age groups, while more female patients were in the adult groups. Both the sIgE levels and the positive rates (approximately 60%) against Der p 1/Der f 1 and Der p 2/Der f 2 were higher than for the Der p 7, Der p 10, and Der p 21 components (below 25%). The Der f 1 and Der p 2 positive rates were higher in 2–12-year-old children. The Der p 2 and Der f 2 IgE levels and positive rates were higher in the allergic rhinitis group. The positive rates of Der p 10 increased significantly with age. Der p 21 is relevant in allergic dermatitis symptom, while Der p 23 contributes to asthma development. Conclusion HDM groups 1 and 2 were the major sensitizing allergens, with group 2 being the most important component relevant to respiratory symptoms in North China. The Der p 10 sensitization tends to increase with age. Der p 21 and Der p 23 might be associated with the development of allergic skin disease and asthma, respectively. Multiple allergen sensitizations increased the risk of allergic asthma.